Assessment of agricultural information needs in African, Caribbean and Pacific (ACP) States for CTA’s Products & Services: Phase 1: Pacific: Country study: Cook Islands - Mataio, Ngatokorua (Technical Centre for Agricultural and Rural Cooperation, 2004)
The current study was initiated by CTA to to provide more targeted assistance to their beneficiaries. In this respect, the study was undertaken to assess the agricultural information needs in the Cook Islands...